Effect of Liquidity, Solvency, Profitability and Market Ratio on Stock Price - Rivi Suci Fahriyana; Sari Puspitarini (Universitas Mercu Buana, 2023)
The purpose of this study was to analyze and examine the effect of Liquidity Ratio (CR), Solvency Ratio (DER), Profitability Ratio (ROE) and Market Ratio (EPS) on Stock Prices in Manufacturing Companies in the Food and Beverage Sub-Sector Listed on the Indonesia Stock Exchange Period 2016-2020. Investors or potential investors must analyze the stock price first so that there are no mistakes when investing because the movement of a company's stock price cannot be easily predicted. So it is necessary to know what things can affect stock prices. The data in this study were obtained from the financial statements of 14 manufacturing companies in the food and beverage sub-sector with secondary data collection techniques using panel data regression with eviews 10 software. The results of the study showed that CR, DER, and ROE had a positive effect and did not have a significant effect. to stock prices. While the EPS variable has a positive and significant effect on stock prices